Long‐term quality of life & functional outcomes after treatment of oropharyngeal cancer. (4th December 2020) - Scott, Susanne I.; Kathrine Ø. Madsen, Anne; Rubek, Niclas; Charabi, Birgitte W.; Wessel, Irene; Fredslund Hadjú, Sara; Jensen, Claus V.; Stephen, Sarah; Patterson, Joanne M.; Friborg, Jeppe; Hutcheson, Kathrine A.; Kehlet, Henrik; et al.
Abstract: Functional and QoL outcomes were compared longitudinally in a cohort of patients treated for oropharyngeal squamous cell carcinoma (OPSCC) with primary transoral robotic surgery (TORS) or radiotherapy (RT). Forty‐four patients undergoing primary TORS (n = 31) or RT (n = 13) for any stage OPSCC were included. Only low‐stage disease was treated with TORS. Functional outcomes were: salivary flow rate, image‐based swallowing function, and a self‐reported 10‐point scale comparing current swallowing function to baseline (CvB scale). QoL was assessed with European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core (EORTC QLQ‐C30), Head & Neck Module (EORTC QLQ‐HN35), and MD Anderson Dysphagia Inventory (MDADI). Shoulder impairment was assessed with Neck Dissection Impairment Index (NDII) and Oxford Shoulder Score (OSS). In the RT group, salivary flow rates had significantly declined at 12‐month follow‐up, with the biggest declines in QoL subscale scores recorded in the RT group for dry mouth and sticky saliva. Swallowing function on imaging studies was overall good, with no severe dysphagia within 1 year although, both treatment groups showed significant deterioration relative to baseline at the 12‐month follow‐up with increased DIGEST scores and pharyngeal retention. Shoulder impairment was rare at 1 year in both groups. A comprehensive examination of this cohort treated for OPSCC showed overall good functional and QoL outcomes 1 year after treatment. However, persistent impairment was seen in both groups with regards to swallowing function. In the TORS group, at 12‐months follow‐up, the QoL questionnaires showed worse scores in only one subscale (sticky saliva). Abstract : In this detailed study of functional and quality of life, 1 year after treatment of oropharyngeal squamous cell carcinoma with either transoral robotic surgery (n = 31) or radiotherapy (n = 13). Functional outcomes were overall good, but persistent impairment was seen in both groups particularly with regards to swallowing function. Worsening in salivary outcomes were seen after treatment with radiotherapy.